Warna Islam Nusantara - Nurul Friskadewi (Institut Islam Nahdlatul Ulama Temanggung, 2017)
Some socio cultural development phenomenon in Indonesia recently is very contrast with modernity dynamic. A numbers of Islamic group in Indonesia are not become more modern, progressive, tolerance and peaceful, but more become stodgy, conservative, intolerance and radical. The Islamic in Indonesia today, especially in some urban area filled advent with various extreme Islamic organizations that anti paced with religious minority, non-Muslim, other religious sect, others Islamic sect, and other local religious belief. Are those many social cultural phenomenons that very contrast in Muslim majority state shows that Islamic Society become more modern or euphoria to become classic even primitive community? Especially for those, who likes to acts barbarous and violence’s. In this essay, I am eager to interpretation this phenomenon by observing community structure, where in the beginning religious community are built as an effort from community to support all individual remain intact and develop in the middle of cultural atmosphere. This community develop in to organization with religious cultural and inequality social aspiration background. And today have developed in to institution and intellectual group that related to educated Muslim middle economic class growth in Indonesia as a whole .I attempt to have dialogist approach on what is happen in the past and what is happen in the present, in to Islamic thought which more less may analyse why this violence phenomenon appears. I am attempt to rewind what is happen in the past, it is impossible that anything might happen without any causes. Taufik Abdullah, Geertz, Kuntowijoyo, Sumanto Al-Qurtuby, Kersten, Nurcholis Madjid, Nico Kaptein, and many others authors are very relevant in perceive this situation. I am also observing the role Islamic intellectual in international arena. I imagine this social phenomenon in form of sketch where Islamic idea still an evolve process. This essay is not meant to prescribe truth to be reconstructed, but to embrace historical fairness that may disclosed. At least in this discourse become initiation to move forward. Like Kersten have suggested, Indonesia Islamic contemporary idea may calls in postmodern stages. He seen Indonesia as unique sites that being mark with struggled to unify norms and value that the sources are from Islam, local culture and international public life’ John Bowen (2003),’transforming Indonesia as one major sites in earth to review social diversity, political idea and religious commitment. Meanwhile tradition institution in traditional view may formulate as channel in process of Islamic domestication and Islamic transition or traditions become indigenous channel. In my point of view, diversity will become complement in Indonesia full colour spectrum of community life. Tug, struggle and dispute in Indonesian Islamic idea will continue in the future. It may become good tradition if this dispute not based on prejudice and hostility, but conversely with mutual respect even though disagree with certain pattern of ideas.